PODIFORM CHROMITITES AND FE-CU-NI-CO MINERALS ASSOCIATED WITH THE BOU AZZER-EL GRAARA OPHIOLITE (CENTRAL ANTI-ATLAS, MOROCCO) - Wafik, Amina; Saquaque, Ali; El Boukhari, Abdelmajid (Ofioliti, 2001)
The presence of chromitites pods within tectonites renders particularly interesting the Proterozoïc ophiolite of Bou Azzer The chromitites are some centimeters to over than ten meters thick and twenty to thirty meters wide, and they spread several dozen of meters in length. They are either concordant (N110 to N130E dominant direction) or discordant (about 30°) on the primary magmatic structures (S0) of harzburgites. Their study reveals primary inclusions of metallic phases in the crystals of chromite. The analysis of these phases with the electronic microprobe (Camebax, laboratory of Petrology, Paris VI, France) and with the MEB (Reminex laboratory, Mine of Guemassa, ONA, Morocco), give the following compositions for the metal sulfides and alloys: – Pyrite FeS2 slightly impoverished in Fe – Chalcopyrite CuFeS2 enriched in S (55.20% atomic) – Galena PbS – Arsenopyrite FeAsS, enriched in S (40.61 % atomic) – Millerite NiS, to cobaltiferous pentlandite Ni3(Co,Fe)2 S5 slightly enriched in sulfur, to Ni3(Co,Fe)2-x S5+x – CoAsS2 (structure analogue to that of skutterudite CoAs3) – (Co,Fe)(As,S) glaucodot – alloys range from Fe0.9Cu0.1 to Cu-Fe-Ni-As more complex compounds with or without S. All these minerals contain some hundreds ppm of Pt and/or Pd as trace elements. In the serpentine minerals, at the border of chromite crystals, other secondary alloys of Fe-Cu-Sn-Co-As-Ag and S occur. These compounds vary from Fe6(Ni,Cu,Ag)4-x(Sn,S,As)x to Fe9(Ni,Cu,Ag)1-x(Sn,S,As)x, and are often associated with interstitial serpentine. The enrichment in Ag and Sn of these alloys is secondary, and it could be contemporary to the serpentinization events related to the hydrothermal circula